COMBAT STRESS AND NEED FOR DEVELOPMENT OF TRAUMA PSYCHIATRIC SERVICES IN PAKISTAN ARMED FORCES: Combat Stress - Ali, Sohail (Pakistan Armed Forces Medical Journal, 2006)
INTRODUCTION War is one of the worst man-made disasters, the sequelae of which continue to influence and haunt people not only in their lifetime but also leaving an impact on the generations to come. Destruction of life and property is only one aspect of the war. What happens to millions of those who come back from the war, is an issue, which is often ignored. The soldiers are driven by their instincts, ambitions, motivations, fears and submission to the cause of war. The concept Combat Stress encompasses these very issues. Stress is viewed as a phenomenon, which afflicts both the victors and the defeated. It addresses the changes that are seen in the soldiers during and after wars. Management of this stress improves combat performance, restores health and rehabilitates the precious soldier. The western countries have taken the initiative in identifying and managing these issues. The British Army during Word War-I collected the first scientific data [1], but thereafter, World War-II, Korean, Vietnam, Arab-Israel War, Falklands and Gulf wars have provided valuable data on the subject. The average figure for the Stress-related Casualties during these wars has been reported to be around 40% [2]. Pakistan Army has also experienced at least three wars, multiple low intensity conflicts and a persistent ongoing active deployment. We have not been able to address the issue of Combat Stress in our veterans merely because of our ignorance to the concept. The battleground of Siachin, skirmishes of Kashmir and the special operations on foreign grounds (UN missions) are descriptive of stories related to stress of combat.